UTILIZATION OF PHOTO STORY MEDIA IN LEARNING TO WRITE NARRATIVE ARRANGEMENTS GENRE-BASED APPROACH - Abdul Azis; Sumarni Sumarni (Universitas Negeri Makassar, 2022)
This study aims to describe the ability of students to write narrative essays based on a genre-based approach using MPS and using video. This research is an experimental research. The population of this research is the students of Class X SMA DDI Maros, Maros Regency totaling 128 people. The sampling technique was random sampling, selected Class X-1 (experimental class) and Class X-3 (control class). The research data is in the form of writing a narrative essay based on a genre-based approach. The collected data were analyzed using descriptive statistical techniques and inferential statistics. The results showed that students' writing skills using photo story media proved to be more effective. Based on the acquisition of the mean score reached 84.00 (experimental class) while students who received video media obtained an average score of 59.71 (control class). Hypothesis testing through parametric inferential statistical analysis type independent sample T test obtained 8.111> 2.00 which indicates that H0 is rejected and H1 is accepted.